2015
DOI: 10.1073/pnas.1501327112
|View full text |Cite
|
Sign up to set email alerts
|

Circadian control of innate immunity in macrophages by miR-155 targeting Bmal1

Abstract: The response to an innate immune challenge is conditioned by the time of day, but the molecular basis for this remains unclear. In myeloid cells, there is a temporal regulation to induction by lipopolysaccharide (LPS) of the proinflammatory microRNA miR-155 that correlates inversely with levels of BMAL1. BMAL1 in the myeloid lineage inhibits activation of NF-κB and miR-155 induction and protects mice from LPS-induced sepsis. Bmal1 has two miR-155-binding sites in its 3′-UTR, and, in response to LPS, miR-155 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
260
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(281 citation statements)
references
References 33 publications
20
260
1
Order By: Relevance
“…REV-ERBs are capable of repressing Bmal1 transcription [20], whereas RORs cause transcriptional activation of Bmal1 [21]. It is believed that post transcriptional modifications, including control by miRNAs [22], provide another layer of organisation to this tightly regulated system. The BMAL1:CLOCK heterodimer can bind thousands of sites in the genome and it is the oscillation of this binding that leads to circadian expression of clock-controlled genes.…”
Section: The Clockwork Machinerymentioning
confidence: 99%
See 2 more Smart Citations
“…REV-ERBs are capable of repressing Bmal1 transcription [20], whereas RORs cause transcriptional activation of Bmal1 [21]. It is believed that post transcriptional modifications, including control by miRNAs [22], provide another layer of organisation to this tightly regulated system. The BMAL1:CLOCK heterodimer can bind thousands of sites in the genome and it is the oscillation of this binding that leads to circadian expression of clock-controlled genes.…”
Section: The Clockwork Machinerymentioning
confidence: 99%
“…• 30% increased weight gain on high fat diet [80] • Increased susceptibility to sepsis with LPS or Listeria [22,65] • Greater IL-6, TNF␣ [22] • Lower IL-10 [22] Clock Global • Partial diabetes [160] • Reduced NF-B activation in MEFs and BMDMs. [66,116] Clock 19 Global • Obese and display impaired glucose sensitivity with insulin resistance and reduced islet size [112,113] • Increased plasma triglyceride and glucose levels [85,114] • Increased fibrotic damage in model of pulmonary fibrosis [87] • Impaired anti-oxidant defense [87] Cry1/Cry2 Global • Increased NAD+ and ATP.…”
Section: Bmal1-a Master Regulatormentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we elucidated the feasibility of using our constructed miRNA reporter imaging system to monitor the location and magnitude of expression levels of miR‐22 in cardiac hypertrophy in vitro and in vivo 19. Most recently, miR‐155 was reported to be expressed in atherosclerotic plaques and proinflammatory macrophages and the in vivo function of miR‐155 in cardiomyocyte hypertrophy was also manifested 20, 21, 22. Another excellent study in this research area by Shyam's group demonstrated a previously unknown role for BRCA1 in epigenetic control of miR‐155 23…”
mentioning
confidence: 99%
“…Above all, the epigenetic alterations in NPSA2 expression may be the primary cause of changes in Bmal1 and Bmal2 in the leukocytes of PD patients [96]. Curtis AM et al identified the importance of Bmal1 in modulating the inflammatory response, by regulating miR-155 and some proinflammatory cytokines including TNF-a [97].…”
Section: Clock Gene Differencementioning
confidence: 99%